Processing of cured cold smoked skipjack and its shelflife at different storage temperature. - Nieto, Rhona G. (College of Fisheries, University of the Philippines, 1993)
In view of the present trend in food production, processing of cured cold-smoked skipjack, which can compete with smoked tangigue in terms of quality and acceptability, was standardized. The final product was established by determining the a(affect of brining time on texture, color, flavour and general acceptability of the product, b) effect of lambanog, a local wine incorporated in the curing solution, on flavour and c) effect of proper handling technique on the "fluorescence" formation. Shelf life study was conducted by packing the products in styropore trays sealed with saran. The products were then stored for 28 days at 3 different temperatures such as 30 degree C, 10 degree C and 0 degree C. physic-chemical tests and sensory evaluation were conducted through random sampling. The study revealed that the cured cold-smoked skipjack, when stored at 30 degree C is acceptable only until the 3rd day of storage. Those stored at 10 degree C and 0 degree C can be kept for 28 days, but the products are more stable at 0 degree C than at 10 degree C.